2019
DOI: 10.1016/j.icarus.2019.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Global seasonal variations of the near-surface relative humidity levels on present-day Mars

Abstract: We investigate the global seasonal variations of near-surface relative humidity and relevant attributes, like temperature and water vapor volume mixing ratio on Mars using calculations from modelled and measurement data. We focus on 2 am local time snapshots to eliminate daily effects related to differences in insolation, and to be able to compare calculations based on modelling data from the Laboratoire de Météorologie Dynamique Mars General Circulation Model with the observations of Mars Global Surveyor Ther… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 47 publications
0
19
0
1
Order By: Relevance
“…The LMD GCM simulates water and dust transport, including the microphysics and radiative effects of water ice clouds, dust/ice sedimentation and condensation/ sublimation of water/ice at the surface [63][64][65][66][67] . The model has also been used to predict and analyze the night-time near-surface relative humidity on Mars 68 . The model is continuously confronted with available observations to validate its results.…”
Section: Methodsmentioning
confidence: 99%
“…The LMD GCM simulates water and dust transport, including the microphysics and radiative effects of water ice clouds, dust/ice sedimentation and condensation/ sublimation of water/ice at the surface [63][64][65][66][67] . The model has also been used to predict and analyze the night-time near-surface relative humidity on Mars 68 . The model is continuously confronted with available observations to validate its results.…”
Section: Methodsmentioning
confidence: 99%
“…Egy marsi év leforgásának illusztrációja, rajta az északi félteke évszakainak jelentős fordulóival (ezekkel egy időben a déli féltekén ellentétes évszak van), valamint a napközel (perihélium), naptávol (aphélium) és a porviharos időszak megjelölésével. A marsi év előrehaladtát általában az ábrán is feltüntetett, szoláris hosszúságban (Ls°) mérik (Pál et al, 2019) szatér. A két félteke ily módon eltérő évszakait a Mars erősen elnyúlt, excentrikus pályájával (1. ábra), illetve a keringési sebesség ezzel járó változásaival lehet magyarázni -ugyanakkor a déli pólussapka nyáron is megmaradó szén-dioxid fedőrétege magas albedójának (fényvisszaverő képességének) kialakulása még pontosan nem tisztázott.…”
Section: A Marsunclassified
“…(i) the low thermal inertia and temperature, which allow the increment of humidity level or by (ii) movements on the Martian surface [17].…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that deliquescence in specific Martian regions could be provided by: the low thermal inertia and temperature, which allow the increment of humidity level or by movements on the Martian surface [ 17 ]. …”
Section: Introductionmentioning
confidence: 99%